2012
DOI: 10.1007/s00227-012-2057-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification on escape performance of the king scallop, Pecten maximus, from Norway

Abstract: The ongoing process of ocean acidification already affects marine life, and according to the concept of oxygen and capacity limitation of thermal tolerance, these effects may be intensified at the borders of the thermal tolerance window. We studied the effects of elevated CO 2 concentrations on clapping performance and energy metabolism of the commercially important scallop Pecten maximus. Individuals were exposed for at least 30 days to 4°C (winter) or to 10°C (spring/summer) at either ambient (0.04 kPa, norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 66 publications
8
66
4
1
Order By: Relevance
“…In the shelled mollusc species studied to date, most of the observations fall within the first set (Parker et al 2009(Parker et al , 2010Lannig et al 2010;Hale et al 2011;Lischka et al 2011;Schalkhausser et al 2012), in line with the hypothesis that CO 2 causes a narrowing of thermal windows (Pörtner and Farrell 2008). These observations have ecosystem implications.…”
Section: Synergistic Impactssupporting
confidence: 69%
See 1 more Smart Citation
“…In the shelled mollusc species studied to date, most of the observations fall within the first set (Parker et al 2009(Parker et al , 2010Lannig et al 2010;Hale et al 2011;Lischka et al 2011;Schalkhausser et al 2012), in line with the hypothesis that CO 2 causes a narrowing of thermal windows (Pörtner and Farrell 2008). These observations have ecosystem implications.…”
Section: Synergistic Impactssupporting
confidence: 69%
“…As a general principle, the thermal windows of marine ectotherms, which shape their range of biographical distribution, are likely to narrow under ocean acidification (Pörtner and Farrell 2008). Nevertheless, it has to be stressed that the majority of the experiments showed that pH within the range projected for the century has no effect on respiration rates of shelled molluscs (Lannig et al 2010;FernandezReiriz et al 2012;Liu and He 2012;Schalkhausser et al 2012).…”
Section: Other Physiological Processesmentioning
confidence: 99%
“…Further, a decrease of pH e in response to ocean acidification in marine invertebrates is also a well-reported phenomenon (e.g. Lannig et al, 2010;Parker et al, 2013;Schalkhausser et al, 2013). In this study, the pH e of oysters dropped approximately 0.2 units when they were kept subtidally and under elevated P CO2 .…”
Section: Condition Indexsupporting
confidence: 65%
“…While ocean acidification appears to have varying and in some cases no effect on metabolism (Bibby et al, 2007;Marchant et al, 2010;Melatunan et al, 2011;Wood et al, 2011;Catarino et al, 2012;McElroy et al, 2012;Manríquez et al, 2013;Matoo et al, 2013;Schalkhausser et al, 2013Schalkhausser et al, , 2014Zhang et al, 2014), a range of other important effects in molluscs, both physiological (reviewed by Parker et al, 2013;Kroeker et al, 2014) and behavioural (e.g. Vargas et al, 2013;Spady et al, 2014;Watson et al, 2014), have been described.…”
Section: Effects Of Ocean Acidificationmentioning
confidence: 99%